Design and manufacture of high-filling-efficiency microfluidic devices - Wu, Chun-Te; Wang, Gou-Jen (International journal of advanced manufacturing technology, 2018)
In this study, we proposed an efficient method for mass production of high-filling-efficiency microfluidic devices. Precision machining was the main process of device fabrication. The commercially available SolidWorks software was adopted for structure design. Unigraphics software was then used to simulate the machining process. The simulated tooling file was then loaded into a CNC milling machine for mold production. The fabricated metal mold was used for pouring polydimethylsiloxane (PDMS) to obtain high-filling-efficiency microfluidic structures. Finally, plasma-assisted packaging was conducted to tightly bind the PDMS microfluidic structure to the glass substrate. Experimental results showed that the additional semicircular filling structure and expended fill-entry structure can efficiently enhance filling efficiency of the microchannel device. The incubation well array can be completely filled at a relatively short filling time. The proposed highly efficient filling microfluidic device possesses advantages, such as feasibility for mass production and cost effectiveness.